Bhartṛprapañca and the Eight States of Brahman - Ivan Andrijanić (Universidad de San Buenaventura, 2016)
A gradual evolution of Brahman in eight successive states is described and criticized in Śaṅkara’s commentary on Bṛhadāraṇyaka-Upaniṣad and in Sureśvara’s and Ānandagiri’s sub-commentaries where the teaching is attributed to Bhartṛprapañca, an ancient Bhedābhedavādin whose commentary on BĀU is now lost. This paper examines fragmentary records of the teaching of Brahman’s evolution and tries to interpret different categories mentioned in different accounts of the teaching by comparing these terms with same or similar categories in other philosophical and religious systems of ancient India in order to understand Bhartṛprapañca’s original eight-fold scheme and its meaning. Tentative conclusion might be that Ānandagiri conveyed Bhartṛprapañca’s scheme literally while Śaṅkara and Sureśvara paraphrased it very freely.